2012
DOI: 10.1158/1078-0432.ccr-12-0127
|View full text |Cite
|
Sign up to set email alerts
|

Spleen Cells from Young but Not Old Immunized Mice Eradicate Large Established Cancers

Abstract: PurposeSolid tumors that have grown two weeks or longer in mice and have diameters larger than 1 cm are histologically indistinguishable from autochthonous human cancers. When experimental tumors reach this clinically relevant size, they are usually refractory to most immunotherapies but may be destroyed by adoptive T cell transfer. However, TCR-transgenic T cells and/or tumor cells overexpressing antigens are frequently used in these experiments. Here we studied the requirements for destroying clinical size, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…45 Schreiber, et al also demonstrated that spleen cells from young but not old immunized mice could eradicate large established cancers. 46 Therefore, young patients with better immune function results show improved clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…45 Schreiber, et al also demonstrated that spleen cells from young but not old immunized mice could eradicate large established cancers. 46 Therefore, young patients with better immune function results show improved clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The retrospective analysis of melanoma patients responding to immunotherapy supports the data from experimental cancer models [2,53**]. A patient with a partial regression following anti-CTLA4 monoclonal antibody (mAb) treatment revealed a dominant CD8 T cell response against a mutant epitope [29*].…”
Section: High Affinity Of Mutant Peptides To Mhc I Required For Cancementioning
confidence: 83%
“…The same case can be made for the Darwinian selection of cancer cells lacking the rejection antigen by a regressor tumor transplanted into normal immunocompetent mice. Such a selection occurs in many different transplant settings [2,26,37,50]. Similar to the above-mentioned sporadic cancer model, T cells did not impair tumor development in a transposon-based autochthonous cancer model [51].…”
Section: Mutant Epitopes Can Be Retained In Patients Despite Specificmentioning
confidence: 92%
See 1 more Smart Citation
“…We have read with great interest the recent study by Schreiber and colleagues (1) in the May 1, 2012 issue of Clinical Cancer Research. This article elegantly uses a naturally induced tumor (8101 tumor) containing a mutated high MHC-binding epitope (p68) from RNA helicase as a target for adoptive cell therapy with tumor sensitized T cells from young or old mice.…”
Section: Laszlo Radvanyimentioning
confidence: 99%